PENERAPAN KEADILAN RESTORATIF DALAM PENYELESAIAN MASALAH TINDAK PIDANA OLEH BHABINKAMTIBMAS POLRI DI PROVINSI LAMPUNG - Edi Setio Budi Santoso, (2021)
Restorative justice is a concept or an approach emphasizing on restoring loss caused by criminal offenses through cooperative processes involving all interested parties. Restorative justice within Indonesian National Police (Polri) can be done before or after investigative processes. Before an investigative process, restorative justice can be done by a bhabinkamtibmas officer (a police sergeant supervising security and public order in a village) who is in-charge of community policing duties as regulated by Polri Chief No. 3/2015 on Community Policing. In Lampung province, the application of restorative justice is supported by an institution, called Rembug Pekon. The problem of the research is about the application of restorative justice done by a bhabinkamtibmas officer and factors influencing such applications. The research is normative juridis. Data is gathered trough literature studies and it is then analyzed quantitively. The results of the research reveal that the applications of restorative justice through Rembug Pekon in villages in Lampung, involving bhabinkambtibmas officers, babinsa officers (military sergeants supervising security and public order of a village) and head of villages is effective enough because is it recognized by community and endorsed by Lampung Bylaw No. 1/2016 on Guidance for Village Coordination in Preventing Conflicts in Lampung Province. Meanwhile, factors influencing the applications of restorative justice are the necessity of having a stronger law baseline in a form of police regulation, empowering bhabinkamtibmas officers (additional officers), improving bhabinkamtibmas officers' communication and mediation skills, and increasing the understanding of bhabinkamtibmas officers on the philosophy of restorative justice.